Algae as a potential source of protein meat alternatives - Espinosa-Ramírez, Johanan; Mondragón-Portocarrero, Alicia C.; Rodríguez, Jose A.; Lorenzo, Jose M.; Santos, Eva M. (Frontiers in Nutrition, 2023)
With the rise of plant-based meat alternatives, there is a growing need for sustainable and nutritious sources of protein. Alga is a rich source of protein, and initial studies show that it can be a good component in the development of plant-based meat alternatives. However, there are certain limitations in their use as the need for efficient and optimal technical processes in large-scale protein extraction and purification, as well as overcoming certain negative effects such as the presence of potentially harmful compounds, allergenicity issues or sensorial affections especially in color but also in textural and flavor characteristics. This review offers a vision of the fledgling research about using alga protein in the development of meat alternatives or supplementing meat products.